Fluoxetine or Sox2 reactivate proliferation-defective stem and progenitor cells of the adult and aged dentate gyrus. (October 2018) - Micheli, Laura; Ceccarelli, Manuela; D'Andrea, Giorgio; Costanzi, Marco; Giacovazzo, Giacomo; Coccurello, Roberto; Caruso, Carla; Tirone, Felice
Abstract: The dentate gyrus of the hippocampus and the subventricular zone are neurogenic niches where the production of new neurons from glia-like stem cells continues throughout adult life. It is not clear whether the pool of stem cells is fated to be exhausted or is conserved until old age. We observed that the antiproliferative gene Btg1 maintains the quiescence of stem cells, and its ablation causes an increase of stem/progenitor cells proliferation in neonatal mice followed by progressive loss of proliferation during adulthood. Fluoxetine is an antidepressant, which exerts a powerful neurogenic effect on dentate gyrus progenitor cells, but is ineffective on stem cells. Here we show that adult dentate gyrus stem cells in the Btg1 knockout mice, with reduced self-renewal and proliferative capability, can be reactivated by fluoxetine, which increases their number greatly above the level of control or fluoxetine-treated wild-type mice. The increase of mitotic index above wild-type in Btg1 knockout fluoxetine-treated stem cells indicates that fluoxetine forces quiescent stem cells to enter the cycle. Stem cell proliferation undergoes continuous reactivation until fluoxetine is administered. Remarkably, fluoxetine reactivates proliferation-defective stem cells also in aged Btg1 knockout mice (15-month-old), an effect absent in wild-type aged mice. Moreover, overexpression of Sox2 retrovirally transduced in Btg1 knockout dentate gyrus cells significantly increases the number of neuroblasts, indicating that Sox2 is able to promote the self-renewal of proliferation-defective stem cells. Overall, the deletion of an antiproliferative gene, such as Btg1, reveals that dentate gyrus stem cells retain a hidden plasticity for self-renewal also in old age, in agreement with a model of permanent self-renewal. Highlights: Fluoxetine activates proliferation-defective stem cells of the adult hippocampus. Fluoxetine stimulates the amplification of stem cells also in aged hippocampus. The stem cells generated after fluoxetine stimulus mature into new neurons. Sox2 rescues the proliferation-defective stem cells of the adult hippocampus.